PENATALAKSANAAN MANAJEMEN NYERI PADA PASIEN KANKER DI RSU SEMBIRING DELI TUA - Herri Novita Tarigan; Megawati Sinambela (INSTITUT KESEHATAN DELI HUSADA, 2021)
Cancer is a disease or abnormalities of cells that grow new abnormally, excessively, uncontrollably, and finally can attack and spread to other organs around it. The pain always impairs cancer patients, it will differentially impair cancer patients', from mild, moderate, and severe. The pains can be overcome according to their standard: mild pain with nonpharmacology as an independent area of nursing, moderate pain with non-pharmacological and pharmacological combinations, they are collaborative areas, and severe pain with pharmacology, it is commonly given with medication. Objective of the Study to find the description of pain management towards cancer patients in RSU Sembiring. The design used was descriptive quantitative with cross-sectional approach, the sample size was 124 people. The sampling technique was Cluster-random sampling. The research instrument used was questionnaire sheet, while the analysis used was descriptive statistics to be displayed in the form of frequency distribution. Description of the implementation of pain management scales 1-3 by nurses towards cancer patients in RSU Sembiring quantitatively on medical records shows that the average achievement of 95.16% (Good), quantitatively in the patients shows that the average achievement of 75.8% (Poor). Description of the implementation of pain management towards cancer patients in RSU Sembiring generally shows fair category.